2013
DOI: 10.1073/pnas.1310153110
|View full text |Cite
|
Sign up to set email alerts
|

Fe–N 2 /CO complexes that model a possible role for the interstitial C atom of FeMo-cofactor (FeMoco)

Abstract: We report here a series of four-and five-coordinate Fe model complexes that feature an axial tri(silyl)methyl ligand positioned trans to a substrate-binding site. This arrangement is used to crudely model a single-belt Fe site of the FeMo-cofactor that might bind N 2 at a position trans to the interstitial C atom. Reduction of a trigonal pyramidal Fe(I) complex leads to uptake of N 2 and subsequent functionalization furnishes an open-shell Fe-diazenido complex. A related series of five-coordinate Fe-CO complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
151
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(166 citation statements)
references
References 45 publications
14
151
1
Order By: Relevance
“…Furthermore, the importance of axial ligand flexibility has also been invoked in mononuclear iron models of the FeMoco cluster of nitrogenase, where the degree of elongation between the axial atom (Si, B, C) of tripodal supporting ligands was speculated to affect the degree of N2 and CO activation. 37 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the importance of axial ligand flexibility has also been invoked in mononuclear iron models of the FeMoco cluster of nitrogenase, where the degree of elongation between the axial atom (Si, B, C) of tripodal supporting ligands was speculated to affect the degree of N2 and CO activation. 37 …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Fe1, the interstitial carbon and molybdenum are no longer aligned, creating an asymmetry in the resulting [7Fe:8S:C:Mo] cluster (Figure 1C). The modest adjustments of the remaining scaffold upon CO binding are suggestive of an important role for the interstitial carbon in stabilizing the cofactor during rearrangements and substitutions to the coordination environment of the irons (34, 35). …”
mentioning
confidence: 99%
“…In 2003, Yandulov and Schrock29303132 reported the first successful example of the catalytic conversion of dinitrogen gas into ammonia using a molybdenum–dinitrogen complex as a catalyst and in 2013 Peters and co-workers33343536373839 reported the iron-catalysed transformation using an iron–dinitrogen complex as a catalyst. We also found that several dinitrogen-bridged dimolybdenum complexes such as [{Mo(N 2 ) 2 (PNP)} 2 (μ-N 2 )] ( 2 ; PNP=2,6-bis(di- tert -butylphosphinomethyl)pyridine)404142 and molybdenum–nitride complexes bearing PNP-type pincer ligands43 or mer -tridentate triphosphine44 worked as more effective catalysts towards ammonia formation under ambient reaction conditions, where up to 63 equiv.…”
mentioning
confidence: 99%